2017
DOI: 10.11648/j.sjee.20170504.12
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Free Glycerol and Glycerides from Biodiesel by Means of Liquid-Liquid Extraction

Abstract: This paper investigates glycerol and glycerides extraction process from fresh and waste sunflower oil biodiesel.Deep eutectic solvent choline-chloride: ethylene-glycol (molar ratio 1:2.5) was used as extraction media in both batch experiments and continuous Karr column. Biodiesel was synthesized in an alkali catalysed chemical transesterification reaction. Three process variables, namely hydrodynamic conditions, solvent to biodiesel ratio and extraction duration were investigated and their impact on the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Uklanjanje zaostalih neželjenih komponenata provedeno je ekstrakcijom pomoću niskotemperaturnog eutektičkog otapala na bazi kolin klorida koje se prethodno pokazalo kao pogodno otapalo za uklanjanje glicerola i glicerida iz sirovog biodizela. 25 Biodizel je sintetiziran pri masenom omjeru KOH : metanol : mast = 1 : 40 : 100. Kako je biodizel ostao u kapljevitom stanju, ekstrakcija je provedena pri sobnoj temperaturi.…”
Section: Sinteza Biodizelaunclassified
“…Uklanjanje zaostalih neželjenih komponenata provedeno je ekstrakcijom pomoću niskotemperaturnog eutektičkog otapala na bazi kolin klorida koje se prethodno pokazalo kao pogodno otapalo za uklanjanje glicerola i glicerida iz sirovog biodizela. 25 Biodizel je sintetiziran pri masenom omjeru KOH : metanol : mast = 1 : 40 : 100. Kako je biodizel ostao u kapljevitom stanju, ekstrakcija je provedena pri sobnoj temperaturi.…”
Section: Sinteza Biodizelaunclassified
“…According to literature [29], extraction efficiency could be enhanced by using a higher temperature. Higher temperatures should reduce glycerol retention, as it was observed in the studies where the effect of temperature on glycerol removal was brought into relation with the concentration factor (CF).…”
Section: Integrated Production and Purification Of Biodiesel-batch Reactor Versus Microreactormentioning
confidence: 99%
“…Taking into consideration that 60-80% of the production costs belongs to the purification steps, it can be concluded that a cheaper and more efficient solution needs to be found [28]. Lately, deep eutectic solvents (DESs) are attracting more and more attention as a potential solution for biodiesel purification [29]. A DES is a binary or ternary mixture consisting of a hydrogen bond donor (HBD) and a hydrogen bond acceptor (HBA), which forms a hydrogen bond [30].…”
Section: Introductionmentioning
confidence: 99%
“…A deep eutectic solvent is formed between a ammonium salt which is a hydrogen bond acceptor and a hydrogen bond donor. The hydrogen bonds between the ions of ammonium salt compound and the hydrogen donors form large and asymmetrical ions which result in a decrease in the melting point of the mixture compared to the melting point of each component [15]. The de-localization of charge that occurs via hydrogen bonding is a major factor in reducing the melting point of the mixture.…”
Section: Deep Eutectic Solventmentioning
confidence: 99%